2006
DOI: 10.1109/jdt.2006.872304
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Performance of Organic Light-Emitting Diodes Containing BCP/LiF/Al by Thermal Annealing

Abstract: Abstract-In this paper, we examined the effect of postpackaging annealing on the performance of organic light-emitting diodes containing tris-(8-hydroxyquinoline) aluminum (Alq 3 ) or 2,9-Dimethyl-4,7-diphenyl-1,10-phenanthroline (BCP) in direct contact with a LiF-Al bilayer cathode. The detailed electroluminescent (EL) characteristics were compared before and after annealing at 70 C for 5 hrs. It was found that better luminous efficiency as well as greater power efficiency could be achieved for devices with B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 27 publications
0
10
1
Order By: Relevance
“…However, our results demonstrated that the performance of devices with appropriate thermal annealing is worse than in case of unannealed device. The achieved result does not agree with those published in the studies by Sun et al, 2006;and Ahn et al, 2005. Different light-emitting polymer may account for this difference.…”
Section: Resultscontrasting
confidence: 80%
See 1 more Smart Citation
“…However, our results demonstrated that the performance of devices with appropriate thermal annealing is worse than in case of unannealed device. The achieved result does not agree with those published in the studies by Sun et al, 2006;and Ahn et al, 2005. Different light-emitting polymer may account for this difference.…”
Section: Resultscontrasting
confidence: 80%
“…Due to the fact that the annealing duration is quite long, interdiffusion between organic layers may occur. This interdiffusion was reported to be helpful for the elimination of heterointerface and, therefore, improves performance of OLED (Sun et al, 2006(Sun et al, , 2005Ahn et al, 2005). However, our results demonstrated that the performance of devices with appropriate thermal annealing is worse than in case of unannealed device.…”
Section: Resultsmentioning
confidence: 59%
“…In particular, recent thermal treatments have shown both sizeable spectral and intensity variations of PL in Alq 3 films [2][3][4][5][6][8][9][10][11][12], and it has also been found that post annealing treatments contribute to better efficiency and lifetime enhancement of OLEDs containing Alq 3 [13][14][15][16][17][18]. However, the above studies are far from being systematic, and hardly clarify the properties of Alq 3 thin films, as far as the consequences of thermal treatments on PL and aggregation processes are concerned.…”
Section: Introductionmentioning
confidence: 99%
“…The corresponding 10 V luminance for this device is less than 30,000 cd/m 2 [41]. The third report has a luminescence of 54,000 cd/m 2 with optimized thicknesses of Ba/Al bilayer cathodes, but the Ba is very sensitive to the environment [42]. the J-V relation (Figure 4), because of the larger effective barrier height of ~0.7 eV at the ITO/TPD interface (insert in Figure 2).…”
Section: Resultsmentioning
confidence: 84%